Karyotype and Growth Analysis of UV-induced Soybean (Glycine max L.) - Elimasni (Talenta Publisher, 2020)
Karyotype and growth analysis of Soybean (Glycine max L.) after exposed to Ultraviolet light had been done. The objective of this research was to investigate karyotype design and vegetative growth of soybean induced with UV light. The experiment was Completely Randomized Designed with 2 treatment factors. The first factor was Ultraviolet light by 3 levels: 10, 20 and 30 Watt and the second was the length of UV exposure by 3 levels: 5, 10, and 15 minutes. Each treatment was replicated 2 times and the plant that was not exposed to UV used as control. The karyotype was observed by squash method. The results showed that the intensity and duration of UV light has no effect on the number of chromosomes but the light has effect on the number of chromosomes type. Statistical analysis showed that the increase in UV energy up to 30 Watt and time exposure of 15 minutes, caused the increase on height, number of leaves, flowers, the fresh and dry weight of plant, and chlorophyll concentration compared to untreated plants.